Global Food Security and Agricultural Natural Resources Role and Views of Argentina, Brazil, Paraguay and Uruguay - Regúnaga, Marcelo (2014)
Presentation by Marcelo Regúnaga, Professor, Universidad de Buenos Aires (Former Secretary of Agriculture, Argentina), IFPRI Policy Seminar: "A Post-Bali Food Security Agenda," May 6, 2104 in Washington, DC.